2007
DOI: 10.1128/jcm.02208-06
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Evaluation of the IDI-MRSA Assay for Detection of Colonization by Methicillin-Resistant Staphylococcus aureus in Diverse Mucocutaneous Specimens

Abstract: Rapid and reliable detection of methicillin-resistant Staphylococcus aureus (MRSA) carriers is crucial for the effective control of MRSA transmission in healthcare facilities. The aim of this study was to verify the performance of the IDI-MRSA real-time PCR assay for direct MRSA detection in diverse mucocutaneous swabs from hospitalized patients. Swabs from nares (n ‫؍‬ 522) and skin or other superficial sites (n ‫؍‬ 478) were prospectively collected for MRSA screening from 466 patients admitted to an 858-bed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
51
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 23 publications
8
51
5
Order By: Relevance
“…Seventeen initially inhibited specimens (1.0%) were eventually included in the data analysis because results were available after freezing and repeating the PCR. Our initial inhibition rate (1.4%) is well in line with that observed by others using Stuart's liquid medium (8,26). Some authors (5,16,17) who used an agar-based medium reported higher inhibition rates and, therefore, pretreated the swabs before performing PCR.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Seventeen initially inhibited specimens (1.0%) were eventually included in the data analysis because results were available after freezing and repeating the PCR. Our initial inhibition rate (1.4%) is well in line with that observed by others using Stuart's liquid medium (8,26). Some authors (5,16,17) who used an agar-based medium reported higher inhibition rates and, therefore, pretreated the swabs before performing PCR.…”
supporting
confidence: 77%
“…This may be explained by the use of enrichment broth as the reference method, which yields conceivably a higher sensitivity than does direct plating (17,20,23). Overall sensitivity of PCR for all swabs (n ϭ 1,595) in Amies agar corresponds well to the results reported previously using Stuart's medium (sensitivity ranging from 81% to 92.3%) (3,8,19,22,26). However, a direct comparison of Amies agar with Stuart's medium for the same clinical specimens has not been undertaken yet.…”
supporting
confidence: 75%
“…The high NPV in this study (97.9%) and those reported by others (7,15,18,21) suggests that this assay provides a rapid method for the identification of persons who are not colonized with MRSA and in that context is likely to be useful for epidemiologic or surveillance activities, whether in a community setting as described in this evaluation or in a health care environment.…”
Section: Downloaded Frommentioning
confidence: 60%
“…One of the reasons for this is the time required for detection, which is still at least 48 h by conventional methods (4,11). A faster MRSA detection method would allow faster interventions and rapid implementation of targeted infection control measures (3,6,9).…”
mentioning
confidence: 99%